An Outbreak of Measles in a University in Korea, 2014 - Choe, Young June (J Korean Med Sci, 2017)
Measles has been declared eliminated from the Korea since 2006. In April 2014, a measles outbreak occurred at a University in Seoul. A total of 85 measles cases were identified. In order to estimate vaccine effectiveness of measles vaccine, we reviewed the vaccination records of the university students. The vaccine effectiveness of two doses of measles containing vaccine was 60.0% (95% CI, 38.2–74.1; P < 0.05). Transmission was interrupted after the introduction of outbreak-response immunization. The outbreak shows that pockets of under-immunity among college students may have facilitated the disease transmission despite the high 2-dose vaccination coverage in the community.